Active wound dressings based on bacterial nanocellulose as drug delivery system for octenidine - Moritz, Sebastian; Wiegand, Cornelia; Wesarg, Falko; Hessler, Nadine; Mueler, Frank A.; Kralisch, Dana; Hipler, Uta-Christina; Fischer, Dagmar (International Journal of Pharmaceutics, 2014)
Although bacterial nanocellulose (BNC) may serve as an ideal wound dressing, it exhibits no antibacterial properties by itself. Therefore, in the present study BNC was functionalized with the antiseptic drug octenidine. Drug loading and release, mechanical characteristics, biocompatibility, and antimicrobial efficacy were investigated. Octenidine release was based on diffusion and swelling according to the Ritger-Peppas equation and characterized by a time dependent biphasic release profile, with a rapid release in the first 8 h, followed by a slower release rate up to 96 h. The comparison between lab-scale and up-scale BNC identified thickness, water content, and the surface area to volume ratio as parameters which have an impact on the control of the release characteristics. Compression and tensile strength remained unchanged upon incorporation of octenidine in BNC. In biological assays, drug-loaded BNC demonstrated high biocompatibility in human keratinocytes and antimicrobial activity against Staphylococcus aureus. In a long-term storage test, the octenidine loaded in BNC was found to be stable, releasable, and biologically active over a period of 6 months without changes. In conclusion, octenidine loaded BNC presents a ready-to-use wound dressing for the treatment of infected wounds that can be stored over 6 months without losing its antibacterial activity. © 2014 Elsevier B.V.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Antiseptic; Hydrogel; Nanocellulose; Octenidine; Wound dressing